(untitled) (Rupandehi Campus Journal, 2022)
Four Noble truths are the foundation for Buddhism and are more significant in Buddha’s teaching. Moreover, the four noble truths and noble eightfold path were taken as a vessel to transcend Buddha’s self-realisation into collective understanding. This paper focuses on investigating the interrelationship between four noble truths using existing mathematical models. The study follows a qualitative research design, inductive approach, and content analysis strategy for collecting and analysing the data. Furthermore, conditional relation and biconditional relation were also applied as a tool for finding the results. The literature suggests that the first major section of four noble truths contains first and second noble truth (related to each other) is related to the realm of death and rebirth whereas the second major section that contains third and fourth noble truths (related to each other) is not the part of cause and effect. However, it was found that the first, second, and fourth noble truths are related to each other by the relation of cause and effect which is shown in mathematical relation (model).